Effect of photo chemical etching and electro chemical etching on the topography of porous silicon wafers surfaces - Amjad Hussein Jassem (Tikrit Journal of Pure Science)
In This research we study the effect of photo chemical etching and electrochemical etching on topography of porous silicon surfaces, the results showed that photo chemical etching produced roughness silicon layer which can have thickness be less of porous silicon layer which is produced by electro chemical etching When all the wafers have same etching time  and hydrofluoric solution (HF) concentration, the wafers have same resistance (10 Ω.cm).